Child protection in Chinese societies: challenges and policies - Chan, Ko-Ling (Children's issues, laws and programs)
Preface -- Child victimization in Chinese societies : current situations -- Child maltreatment in Chinese societies : a comprehensive review / Chan, Ko Ling -- Child victimization in China : prevalence and risk factors / Chan, Ko Ling -- Child victimization in China : interpretation of findings and recommendations / Chan, Ko Ling -- Case study of an adult survivor from child sexual abuse / Ms Choi, Anna Wai Man, & Dr. Chan, Ko Ling -- Legal systems in child protection and related issues -- Legal developments and challenges in child protection in mainland China / Wang, Xuemei -- Juvenile justice reform and child protection system : a China case study / Song, Yinghui, He, Ting, Wang, Zhenhui, Ms Hu, Yuanqiong & Ms Jiang, Min -- Cyberbullying in Hong Kong, Taiwan, and mainland China : in search of a regulatory framework / Cheung, Anne S.Y -- Health and social services in child protection and related issues -- Policies and social services of child protection in mainland China and Hong Kong / Chan, Ko Ling -- Developing a child welfare and child protection system in China : UNICEF support to the government of China / Ng Bow, Lisa -- Child protection in Hong Kong / Ho, Jessica Oi Chu -- The social support system for children orphaned by HIV/AIDs / Cheng, Ling, & Prof. Xiang -- Hospital-based education program for the prevention of child accidental injury / Ji, Qing Ying -- Child protection : future directions -- Children's commission : child protection beyond rhetoric / Ip, Patricia -- Child abuse in Hong Kong and the importance of building an effective surveillance system in Chinese societies / Ip, Patrick, Mr Wong, Wilfred Hing-sang, & Dr. Li, Sophia Ling -- Index